The Greatest Dog Stories Ever Told : Great Writers from Ray Bradbury to Mark Twain Celebrate Man's Best Friend - Edited by Sherwood, Patricia M. (Guilford Lyons Press, 2009)
Thirty unforgettable dog tales by some of the world's finest writers.
Keywords: Dogs -- Literary collections -- American literature -- English literature